Effect of specimen thickness on chromia scaling of Ni25Cr in N2–O2–H2O test gases at 1000°C. (January 2015) - Hänsel, M.; Turan, E.; Shemet, V.; Grüner, D.; Breuer, U.; Simon, D.; Gorr, B.; Christ, H-J.; Quadakkers, W. J.
Abstract : The isothermal oxidation behaviour of a Ni25Cr model alloy was studied using specimens of different thicknesses at 1000°C in dry and wet N2 –1%O2 . The oxidation mechanisms were evaluated using thermogravimetry and SEM/electron backscatter diffraction analyses of oxide scale cross-sections. The oxidation rates decreased with increasing specimen thickness and increasing water vapour additions in the gas. The findings can be explained by considering the effect of H-defects and in-scale stress state on point defect concentrations in the chromia lattice.